Infusing undergraduate research into historically black colleges and universities curricula - McClinton, Jeton (Diversity in higher education ;, 2015)
Undergraduate Research (UGR) is any creative effort undertaken by an undergraduate that advances the knowledge of the student in an academic discipline and leads to new scholarly insights or the creation of new knowledge that adds to the wealth of the discipline. Undergraduate research is valued and encouraged at several HBCUs; however, the history, implementation, nor progress has not been sufficiently published and disseminated nationally. Importantly, a great deal of learning occurs when undergraduate students conduct research and, of course, much of this learning does not happen during the traditional coursework. Research leads to better understanding of and deeper appreciation for the discipline. Further, it is contended that students' career goals and academic expectations are enhanced as a result of research participation. Extensive undergraduate research can increase access to PhD programs. From the voices of faculty mentors, student mentees and UGR program directors and program coordinators this volume describes the successes of programs across HBCUs and discusses how retention and graduation rates have been increased as a result of participation.